THE DILEMMA OF INTEGRATION INTERNALLY DISPLAYED PERSONS IN UASIGISHU COUNTY, KENYA - Mwangi, Kungu, David (European Scientific Journal, ESJ, 2015)
Internal displacements in Africa and Kenya in particular have become a common phenomenon. These have had multiple causes ranging from ethnic conflict, inter clan conflicts, cattle rustling, floods, earth quakes and politically instigated tensions and conflicts. However, of the many causes of internal displacements the most common and notable is the politically instigated conflict as it is perennial, occurring after most elections since the re-introduction of multi-party politics. Such displacements occurred in 1992 and 1997, the worst being the post election violence of 2007 and 2008 following the disputed presidential elections. Therefore, the purpose of this paper is to investigate the challenges to integration of internally displaced persons (IDPs) in Kenya with reference to Uasin Gishu District. The study adopted a survey research design. The target population was 31,189 IDPs in camps, the â€œhostâ€ community who were 289,380, 5 government officers and 5 NGOs giving assistance to IDPs. From these target populations a sample of 100 IDPS in camps, 100 members of the host community, 5 provincial administration officials and 5 representatives of NGOs were drawn using cluster sampling, simple random sampling, transect walk and census sampling. The data were collected using questionnaires and interviews. The quantitative data collected was analyzed descriptively while qualitative data was analyzed using the five thematic steps. The study found out that the main challenges to integration of the IDPS included lack of economic resources, the host community being unfriendly and fluctuating political temperatures at the national and local levels. The study recommends that the process of resettlement and integration of IDPs should be hastened, peace and reconciliation be a continuous process, to ensure that IDPs are economically integrated, they should be given economic support and that all actors should be included in the re-settlement and integration process.